PENGARUH LINGKUNGAN KERJA NONFISIK, DISIPLIN KERJA, DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA USAHA KECIL DAN MENENGAH (UKM) DIMSUM ECHODINNO DI PERTANIAN RAYA - Firlianza Dhifafsari, (2021)
The purpose of this quantitative study is to find out and prove the influence of the non physical work environment, work discipline, and motivation on employee performance in Dimsum Echodinno's Small and Medium Enterprises (UKM) in Greater Agriculture. All sales employees with a total of 60 people constitute the population in this study. Saturated sample or the whole population is a sampling technique in this study, which is as many as 60 respondents. The source of data in this research is using primary data, as well as distributing questionnaires or questionnaires to collect the data. In data analysis, statistical methods are used in the form of Partial Least Square (PLS) using SmartPLS 3.0 software. The results obtained include: (1) the non-physical work environment has a positive and significant effect on the performance of Dimsum Echodinno's SME employees, (2) work discipline has a positive and significant influence on the performance of Dimsum Echodinno's SME employees, and (3) work motivation has an influence positive and significant impact on the performance of SME employees Dimsum Echodinno.